Silicon monoxide composite material and preparation method thereof
By using nitrogen-fluorine doped carbon coating on the silicon oxide material, the problem of volume expansion and poor Coulomb efficiency in lithium-ion batteries is solved, and the electrochemical performance and safety performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202311245139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon oxide materials have problems such as large volume expansion, poor Coulomb efficiency and low material conductivity in lithium-ion batteries, which limit their widespread use in industrial applications.
The nitrogen and fluorine element doping in the carbon coating layer are used to form a nitrogen-fluorine-doped carbon-coated silicon oxide composite material through combination with the silicon oxide material. This method improves the electrochemical performance of the battery by improving conductivity, inhibiting volume expansion and providing more lithium active sites.
The first-time Coulomb efficiency and cycle stability of the silicon oxide composite material are significantly improved, the safety performance of the battery and the electrochemical lithium storage performance are enhanced, and the discharge capacity and first-time discharge efficiency of the battery are improved.
Smart Images

Figure CN119695134A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and particularly relates to a silicon monoxide composite material and a preparation method thereof. Background Art
[0002] In recent years, due to the rapid growth of energy demand in electric vehicles, hybrid electric vehicles, portable electronic devices, etc., the development of lithium-ion batteries (LIBs) with high specific capacity and long life has become a research hotspot. Silicon monoxide (SiO x , 0 < x < 2) as one of the candidates for the next-generation anode materials has a theoretical capacity as high as 2043 mAh g -1 , and has advantages such as a low charge-discharge voltage plateau (<0.5 V vs. Li + / Li), rich natural content (28% of the earth's crust mass), and low toxicity [1,2] . However, problems such as large volume expansion (about 200%), poor Coulomb efficiency, and low material conductivity (6.7×10 -4 S cm -1 ) have limited the industrialization of silicon monoxide to a certain extent [3,4] .
[0003] At present, there are also many reports on the modification of silicon monoxide materials. For example, patent application documents CN110148729A, CN112289993B, CN110176601A, etc. have all disclosed carbon-coated silicon monoxide composite materials. By carbon-coating the silicon monoxide material, while improving the electronic conductivity of the anode material, the volume expansion during the charge and discharge of the silicon monoxide material is inhibited, thereby improving the first Coulomb efficiency and cycle stability performance of the silicon monoxide material.
[0004] However, the simple carbon coating has limited improvement in the performance of the silicon monoxide material. Therefore, heteroatom doping has also been attempted in related technologies. For example, patent application document CN 113816384 A discloses a preparation method and product of a phosphorus-doped porous carbon-coated silicon monoxide material. This preparation method obtains a core-shell structure composite material with a phosphorus-doped porous carbon as the coating layer through high-temperature pyrolysis using phytic acid as the carbon source and phosphorus source. Although phosphorus elements can induce the generation of more defects and edge positions and improve the reaction activity, the conductivity of phosphorus is slightly poor, and the improvement of the electrochemical performance of the material is limited.
[0005] It can be seen that although the current single-element doped silicon-based materials can improve the electrochemical performance by adjusting the electronic structure, chemical bonds, etc., the single-element doping has little effect on the performance improvement and has great limitations; in addition, it cannot solve the problem of volume expansion of silicon dioxide materials. Therefore, many studies have tried to design double heteroatom doping with different functions to improve the electrochemical performance of batteries, and the preparation process is not much more difficult than single-element doping. Therefore, double-element doping has become a new way to achieve large-scale application of silicon dioxide negative electrodes.
[0006] For example, patent application document CN 113471440 A discloses a silicon-oxygen material, its preparation method and use. The raw material for preparing the silicon-oxygen material includes a Si single substance doped with a doping element M, and the doping element M includes any one or a combination of at least two of boron, aluminum, gallium, indium, nitrogen, phosphorus, arsenic or antimony. However, since the doping elements are mostly metal elements, the reaction conditions are harsh and the cost is high. At the same time, there are problems such as low initial discharge specific capacity, capacity retention rate after multiple cycles and coulomb efficiency of the material. In addition, the preparation method of the silicon-oxygen material is to dope the raw material Si single substance with elements of the third main group and / or the fifth main group to change the kinetic properties of the Si single substance, so that when the Si single substance is oxidized and reduced with raw materials such as SiO2 to prepare the silicon-oxygen material, the silicon-oxygen material forms an interface cluster mixing model, in which the Si element has a conductor property, so that the obtained silicon-oxygen material has a higher conductivity. However, the preparation method adopts a solid-solid diffusion method, which has high requirements on experimental conditions and complex operation.
[0007] [1]Ha Y,Stetson C,Harvey SP,et al.Effect of Water Concentration inLiPF6-Based Electrolytes on the Formation,Evolution,and Properties of theSolid Electrolyte Interphase on Si Anodes[J].ACS Appl Mater Interfaces,2020,12(44):49563-49573.
[0008] [2]Shen
[0009] [3]Guo J, Dong D, Wang J, et al. Silicon-Based Lithium Ion BatterySystems: State-of-the-Art from Half and Full Cell Viewpoint[J]. Advanced Functional Materials, 2021, 31(34).
[0010] [4]Liu Z, Yu Q, Zhao Y, et al. Silicon oxides: a promising family of anodematerials for lithium-ion batteries[J]. Chem Soc Rev, 2019, 48(1):285-309. Summary of the invention
[0011] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a silicon oxide composite material and a preparation method thereof.
[0012] The silicon oxide composite material of the embodiment of the present invention comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, wherein the carbon coating layer is doped with nitrogen and fluorine.
[0013] The advantages and technical effects brought by the silicon oxide composite material of the embodiment of the present invention are as follows:
[0014] (1) The carbon coating layer can improve the conductivity of the silicon oxide composite material of the embodiment of the present invention and inhibit the volume expansion of silicon oxide, thereby improving the first coulombic efficiency and cycle stability of the silicon oxide composite material;
[0015] (2) Nitrogen and fluorine doped in the carbon coating can provide more lithium active sites, reduce the migration resistance of lithium ions, and promote the insertion and extraction of lithium ions; effectively inhibit the formation of lithium dendrites and improve the safety performance of the electrode sheet;
[0016] (3) At the same time, compared with the silicon oxide composite material not doped with nitrogen and fluorine or only doped with nitrogen or only doped with fluorine, the silicon oxide composite material of the embodiment of the present invention has higher electronic conductivity and higher electron transmission capacity, and therefore has better electrochemical lithium storage performance, which can improve the discharge capacity and first discharge efficiency of the battery.
[0017] In some embodiments, based on the total mass of the silicon oxide composite material being 100.0 wt %, the mass fraction of the carbon coating layer is 5-14.0 wt %.
[0018] In some embodiments, based on 100.0% of the total atoms of the silicon oxide composite material, the atomic percentage content of the nitrogen element is 0.1-5.0%, and the atomic percentage content of the fluorine element is 0.1-5.0%.
[0019] In some embodiments, the particle size of the silicon oxide composite material is 4.5-20 μm; the particle size of the silicon oxide is 4-10 μm.
[0020] In addition, an embodiment of the present invention further provides a method for preparing a silicon dioxide composite material, comprising the following steps:
[0021] Step 1. Mix a carbon source, a nitrogen source and a fluorine source, react under heating conditions, and then cool and wash the reaction product and mix it with a solvent to obtain a nitrogen-fluorine doped carbon precursor solution;
[0022] Step 2. mixing silicon dioxide with the nitrogen-fluorine-doped carbon precursor solution, and drying to obtain silicon dioxide precursor powder coated with nitrogen-fluorine-doped carbon;
[0023] Step 3: calcining the nitrogen-fluorine-doped carbon-coated silicon oxide precursor powder in an inert gas atmosphere to obtain a nitrogen-fluorine-doped carbon-coated silicon oxide composite material.
[0024] The advantages and technical effects brought by the method for preparing the silicon dioxide composite material according to the embodiment of the present invention are as follows:
[0025] (1) In step 1, a nitrogen-fluorine-doped carbon precursor solution is first obtained, and then mixed with silicon oxide in step 2 to improve the dispersion uniformity of the two, so that the subsequent carbon coating layer can be more evenly coated on the surface of the silicon oxide core; then in step 3, the nitrogen-fluorine-doped carbon-coated silicon oxide precursor powder is calcined in an inert gas atmosphere, so that the nitrogen-fluorine co-doped carbon coating layer is coated on the surface of the silicon oxide core, thereby obtaining the silicon oxide composite material of the embodiment of the present invention. The entire preparation process is relatively simple, the cost is lower, and it is conducive to large-scale production;
[0026] (2) In the prepared silicon oxide composite material, nitrogen and fluorine co-doping can improve the conductivity of the carbon coating layer, so that the composite material has more defect sites and enhances the interaction with the active Li + The reaction can jointly improve the cycle stability of the electrode, and the battery prepared using the composite material of the embodiment of the present invention has excellent electrochemical performance.
[0027] In some embodiments, in step 1, a primary amine compound, formaldehyde and a phenol compound are respectively mixed with the solvent to obtain a primary amine compound solution, a formaldehyde solution and a phenol compound solution, wherein the primary amine compound and / or the phenol compound contain fluorine; the primary amine compound solution, the formaldehyde solution and the phenol compound solution are then mixed and reacted under heating conditions, and then the reaction product is cooled, washed and mixed with the solvent to obtain the nitrogen-fluorine-doped carbon precursor solution.
[0028] In some embodiments, in step 1, the primary amine compound is aniline and / or p-fluoroaniline; and / or the phenol compound includes at least one of phenol, 2-fluorophenol and p-trifluoromethylphenol; and / or the solvent includes at least one of toluene, dioxane, chloroform and DMF.
[0029] In some embodiments, the molar ratio of the primary amine compound, the formaldehyde and the phenol compound in step 1 is (0.8-1.2):(1.8-2.2)2:(0.8-1.2); and / or, the reaction is carried out at 90-100° C. for 5-6 hours.
[0030] In some embodiments, the molar ratio of the silicon oxide to the primary amine compound in step 2 is 1:1-1:3.
[0031] In some embodiments, in step 3, a pre-sintering treatment is first performed at 380-420° C. for 1.5-2.5 h, and then a calcining treatment is performed at 400-900° C. for 1.5-2.5 h. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The scanning electron microscope image (SEM) and energy dispersive spectrometer (EDS) of the silicon dioxide composite material of Example 1;
[0033] Figure 2 The half-cells of Example 1 and Comparative Examples 1-2 were subjected to a current density of 1000 mA g -1 Cycle performance diagram when
[0034] Figure 3 The first cycle charge and discharge performance diagram of the half-cell of Application Example 1 and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0035] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0036] An embodiment of the present invention provides a silicon monoxide composite material, comprising silicon monoxide and a carbon coating layer coated on the surface of the silicon monoxide, wherein the carbon coating layer is doped with nitrogen element and fluorine element.
[0037] The silicon monoxide composite material of the embodiment of the present invention has a core-shell structure, with silicon monoxide (SiO x , 0 < x < 2) as the core and the carbon coating layer as the shell. The carbon coating layer can improve the electronic conductivity of the composite material and inhibit the volume expansion of silicon monoxide; the doping of N element can improve the electronic conductivity of the composite material and enhance the interaction between Li + and the electrode surface; the doping of F element can increase the defect sites of the carbon coating layer and have more Li + active centers; N and F elements replace some of the original lattice positions of C in the carbon coating layer, and their synergistic effect can improve the electrochemical performance of the composite material.
[0038] In some embodiments, based on the total mass of the silicon monoxide composite material being 100.0 wt%, the mass fraction of the carbon coating layer (including N and F) is 5 - 14.0 wt%, such as 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, etc. When the content of the carbon coating layer is too low, it is not conducive to improving the conductivity of the silicon monoxide composite material and is also not conducive to improving the first Coulomb efficiency of the battery. When the content of the carbon coating layer is too high, the content of the silicon monoxide core is too low, which is not conducive to the exertion of the specific capacity of the silicon monoxide composite material.
[0039] In some embodiments, based on the total number of atoms of the silicon monoxide composite material being 100%, the total atomic percentage content of the nitrogen element and the fluorine element is 0.1 - 10.0%, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc. When the total doping amount of the nitrogen element and the fluorine element is too low, it is not conducive to improving the electronic conductivity of the silicon monoxide composite material, and it is also not conducive to increasing the defect sites of the carbon coating layer and the exertion of the function of having more Li + active centers, thus not conducive to improving the discharge capacity and the first discharge efficiency of the battery. When the total doping amount of the nitrogen element and the fluorine element is too high, the carbon content is too low, which is not conducive to inhibiting the volume expansion of silicon monoxide and is not conducive to improving the cycle stability.
[0040] In some embodiments, based on the total atomic number of the silicon oxide composite material as 100.0%, the atomic percentage content of the nitrogen element is 0.1-5.0%, such as 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc., and the atomic percentage content of the fluorine element is 0.1-5.0%, such as 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc. Under the condition that the total doping amount of N and F is constant, when the doping amount of N is too low, it is not conducive to enhancing the Li + When the N doping level is too high, the F doping level will be too low, which is not conducive to increasing the defect sites of the carbon coating layer and making it have more Li + active center, which is not conducive to improving the first coulombic efficiency of the battery.
[0041] In some embodiments, the particle size of the silicon oxide composite material is 4.5-20 μm, such as 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. When the particle size of the silicon oxide composite material is too small, not only will the material cost increase due to processing difficulties, but also the side reactions increase when it is used as a negative electrode material due to the increase in specific surface area. When the particle size of the silicon oxide composite material is too large, it is not conducive to reducing the volume expansion of the material, and thus is not conducive to improving the cycle performance of the material.
[0042] In some embodiments, the particle size of the silicon oxide is 4-10 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. When the particle size of silicon oxide is too small, the particle size of the silicon oxide composite material will also be too small, which will not only increase the material cost due to processing difficulties, but also increase the side reactions when it is used as a negative electrode material due to the increase in specific surface area. When the particle size of silicon oxide is too large, the particle size of the silicon oxide composite material will also be too large, which is not conducive to reducing the volume expansion of the material, and thus is not conducive to improving the cycle performance of the material.
[0043] In addition, an embodiment of the present invention further provides a method for preparing a silicon dioxide composite material, comprising the following steps:
[0044] Step 1. Mix a carbon source, a nitrogen source and a fluorine source, react under heating conditions, and then cool and wash the reaction product and mix it with a solvent to obtain a nitrogen-fluorine doped carbon precursor solution;
[0045] Step 2. mixing silicon dioxide with the nitrogen-fluorine-doped carbon precursor solution, and drying to obtain silicon dioxide precursor powder coated with nitrogen-fluorine-doped carbon;
[0046] Step 3: calcining the nitrogen-fluorine-doped carbon-coated silicon oxide precursor powder in an inert gas atmosphere to obtain a nitrogen-fluorine-doped carbon-coated silicon oxide composite material.
[0047] The preparation method of the embodiment of the present invention first obtains a nitrogen-fluorine doped carbon precursor solution, and then mixes it with silicon oxide, which can improve the dispersion uniformity of the two, so that the subsequent carbon coating layer can be more evenly coated on the surface of the silicon oxide core; then the nitrogen-fluorine doped carbon-coated silicon oxide precursor powder is calcined in an inert gas atmosphere, so that the nitrogen-fluorine co-doped carbon coating layer is coated on the surface of the silicon oxide core, and the silicon oxide composite material of the embodiment of the present invention is obtained. The preparation method of the embodiment of the present invention is simple, has lower cost, and is conducive to large-scale production. In the silicon oxide composite material prepared by the preparation method of the embodiment of the present invention, nitrogen and fluorine co-doping can improve the conductivity of the carbon coating layer, so that the composite material produces more defect sites, and enhances the interaction with active Li + The reaction can jointly improve the cycle stability of the electrode, and the battery prepared using the composite material of the embodiment of the present invention has excellent electrochemical performance.
[0048] In some embodiments, in step 1, a primary amine compound, formaldehyde and a phenol compound are respectively mixed with the solvent to obtain a primary amine compound solution, a formaldehyde solution and a phenol compound solution, wherein the primary amine compound and / or the phenol compound contain fluorine; the primary amine compound solution, the formaldehyde solution and the phenol compound solution are then mixed and reacted under heating conditions, and then the reaction product is cooled, washed and mixed with the solvent to obtain the nitrogen-fluorine-doped carbon precursor solution.
[0049] The Mannich reaction of phenol occurs between primary amine compounds, formaldehyde and phenol compounds, and the reaction product is a benzo six-membered heterocyclic compound - benzoxazine monomer.
[0050] In some embodiments, in step 1, the primary amine compound is aniline and / or p-fluoroaniline; and / or the phenol compound includes at least one of phenol, 2-fluorophenol and p-trifluoromethylphenol.
[0051] In some embodiments, the solvent in step 1 includes at least one of toluene, dioxane, chloroform and DMF. The above solvents are all organic and have good solubility for primary amine compounds, formaldehyde and phenol compounds.
[0052] In some embodiments, the molar ratio of the primary amine compound, the formaldehyde and the phenol compound in step 1 is (0.8-1.2):(1.8-2.2):(0.8-1.2). By controlling the proportion of the raw materials, a silicon oxide composite material with different element doping amounts can be obtained. When the molar ratio of the primary amine compound, the formaldehyde and the phenol compound is within the above range, the doping amounts of N and F in the silicon oxide composite material prepared subsequently are within the preferred range, which is beneficial to improving the electrochemical performance of the battery. Preferably, the molar ratio of the primary amine compound, the formaldehyde and the phenol compound in step 1 is 1:2:1.
[0053] In some embodiments, the reaction is carried out at 90-100° C. for 5-6 hours in step 1. In step 1, the Mannich reaction of phenol occurs. When the reaction temperature is too low, the reaction time is too long, which is not conducive to improving production efficiency. When the reaction temperature is too high, although the reaction time can be shortened, the side reactions increase, which will reduce the conversion rate and is not conducive to the synthesis of nitrogen-fluorine-doped carbon precursors.
[0054] In some embodiments, a heating reflux reaction is performed in step 1. The heating reflux reaction combines high temperature heating and reflux solution, which can quickly and thoroughly react.
[0055] In some embodiments, the molar ratio of the silicon oxide to the primary amine compound in step 2 is 1:1-1:3. By controlling the proportion of the raw materials, the ratio of the silicon oxide core and the carbon coating layer in the silicon oxide composite material can be adjusted. When the molar ratio of silicon oxide to the primary amine compound is within the above range, the ratio of the silicon oxide core and the carbon coating layer in the silicon oxide composite material prepared subsequently is within the preferred range, which is beneficial to improving the electrochemical performance of the battery.
[0056] In some embodiments, in step 3, a pre-sintering treatment is first performed at 380-420° C. for 1.5-2.5 h, and then a calcining treatment is performed at 400-900° C. for 1.5-2.5 h. Pre-sintering treatment first is more conducive to the formation of phases in the subsequent calcining treatment, and improves the purity of the obtained nitrogen-fluorine-doped carbon-coated silicon oxide composite material.
[0057] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.
[0058] Example 1
[0059] A silicon oxide composite material comprises silicon oxide SiO and a carbon coating layer coated on the surface of silicon oxide SiO, wherein the carbon coating layer is doped with nitrogen and fluorine. Based on the total mass of the silicon oxide composite material being 100.0wt%, the mass fraction of the carbon coating layer (including N and F) is 10.0wt%. Based on the total number of atoms of the silicon oxide composite material being 100.0%, the total atomic percentage content of nitrogen and fluorine is 9.0%; the atomic percentage content of nitrogen is 4.0%, and the atomic percentage content of fluorine is 5.0%. The particle size of the silicon oxide composite material is 5μm; and the particle size of silicon oxide SiO is 4μm.
[0060] The preparation method of the above silicon dioxide composite material is as follows:
[0061] Step 1. Prepare nitrogen-fluorine dual-doped carbon precursor solution (N, FC precursor solution).
[0062] Add 0.2 mol aniline, 0.4 mol formaldehyde solution (mass fraction 37%), and 0.2 mol 2-fluorophenol to three portions of toluene solvent, respectively, and mix well to obtain aniline-toluene solution, formaldehyde-toluene solution, and 2-fluorophenol-toluene solution, respectively. First, add aniline-toluene solution and formaldehyde-toluene solution to a three-necked flask with a reflux device, stir at room temperature for 1 hour, slowly add 2-fluorophenol-toluene solution to the three-necked flask with a constant pressure dropping funnel, stir rapidly, and reflux at 100°C for 6 hours. After the reaction is completed, cool naturally, remove the solvent, and use 1.0 mol·L -1 The impurities are removed by adding NaOH solution and deionized water and washed to neutrality, and then placed in toluene to form a uniform and stable clear solution, thereby synthesizing the N,FC precursor solution.
[0063] Step 2. Prepare nitrogen-fluorine dual-doped carbon-coated silicon dioxide precursor powder (N, FC@SiO precursor powder).
[0064] 0.2 mol of SiO2 was weighed and added to the N,FC precursor solution, which was sealed and ultrasonically treated for 6 h to disperse evenly, and then placed in a vacuum drying oven at 60 °C for 24 h to obtain N,FC@SiO2 precursor powder.
[0065] Step 3. Prepare nitrogen-fluorine dual-doped carbon-coated silicon oxide composite material (N, FC@SiO composite material) by high temperature calcination.
[0066] The N, FC@SiO precursor powder was heated from room temperature to 400°C at a heating rate of 4°C / min in an argon atmosphere and maintained for 2 h. Then, the temperature was further increased to 800°C at a heating rate of 4°C / min and maintained for 2 h. The powder was cooled to room temperature to obtain a N, FC@SiO composite material.
[0067] Application Example 1
[0068] A negative electrode was prepared using the N,FC@SiO composite material of Example 1 as the negative electrode active material: the negative electrode active material was mixed with a conductive agent, a binder, and a thickener in deionized water in a mass ratio of negative electrode active material: Super p: CMC: SBR = 7:1:1:1, and the mixture was evenly mixed by magnetic stirring to obtain a viscous negative electrode slurry, which was then evenly coated on a copper sheet and dried under a vacuum environment at 120°C for 8h. Finally, the dried negative electrode sheet was placed on a tablet press and maintained at a pressure of 10MPa for 30s to obtain a prepared negative electrode.
[0069] The dried negative electrode was punched into a circular electrode with a diameter of 12 mm. The lithium sheet was used as the counter electrode and Celgard was used as the separator. The solvent volume ratio was EC (ethylene carbonate): EMC (ethyl methyl carbonate): DMC (dimethyl carbonate) = 1:1:1, and the electrolyte was 1 mol·L -1 LiPF6 electrolyte was used to assemble a CR 2025 button half-cell. The amount of electrolyte added was 40 μL. The entire battery assembly was completed in a glove box.
[0070] Example 2
[0071] A silicon oxide composite material comprises silicon oxide SiO and a carbon coating layer coated on the surface of silicon oxide, wherein the carbon coating layer is doped with nitrogen and fluorine. The total mass of the silicon oxide composite material is 100.0wt%, and the mass fraction of the carbon coating layer (including N and F) is 9.0wt%. The total atomic percentage content of nitrogen and fluorine is 7.5% based on the total mass of the silicon oxide composite material as 100.0%, the atomic percentage content of nitrogen is 2.5%, and the atomic percentage content of fluorine is 5.0%. The particle size of the silicon oxide composite material is 5μm; the particle size of silicon oxide SiO is 4μm.
[0072] The preparation method of the above silicon dioxide composite material is as follows:
[0073] Step 1. Prepare nitrogen-fluorine dual-doped carbon precursor solution (N, FC precursor solution).
[0074] Add 0.15 mol aniline, 0.3 mol formaldehyde solution (mass fraction 37%), and 0.15 mol p-trifluoromethylphenol to three portions of toluene solvent, respectively, and mix well to obtain aniline-toluene solution, formaldehyde-toluene solution, and p-trifluoromethylphenol-toluene solution, respectively. First, add aniline-toluene solution and formaldehyde-toluene solution to a three-necked flask with a reflux device, stir at room temperature for 1 hour, slowly add p-trifluoromethylphenol-toluene solution to the three-necked flask with a constant pressure dropping funnel, stir rapidly, and reflux at 90°C for 5 hours. After the reaction is completed, cool naturally, remove the solvent, and use 1.0 mol·L -1 The impurities are removed by using NaOH solution and deionized water and washed to neutrality, and then placed in toluene to form a uniform and stable clear solution, thereby synthesizing the N,FC precursor solution.
[0075] Step 2. Prepare nitrogen-fluorine dual-doped carbon-coated silicon dioxide precursor powder (N, FC@SiO precursor powder).
[0076] 0.15 mol of SiO2 was weighed and added to the N,FC precursor solution, which was sealed and ultrasonically treated for 6 h to disperse evenly, and then placed in a vacuum drying oven at 60 °C for 24 h to obtain N,FC@SiO2 precursor powder.
[0077] Step 3. Prepare nitrogen-fluorine dual-doped carbon-coated silicon oxide composite material (N, FC@SiO composite material) by high temperature calcination.
[0078] The N, FC@SiO precursor powder was heated from room temperature to 400°C at a heating rate of 3°C / min in an argon atmosphere and maintained for 2 h. Then, the temperature was further increased to 700°C at a heating rate of 3°C / min and maintained for 2 h. The mixture was cooled to room temperature to obtain a N, FC@SiO composite material.
[0079] Application Example 2
[0080] A negative electrode was prepared using the N,FC@SiO composite material of Example 2 as the negative electrode active material, and then assembled into a CR 2025 button half-cell in the same manner as in Application Example 1.
[0081] Example 3
[0082] A silicon oxide composite material comprises silicon oxide SiO and a carbon coating layer coated on the surface of silicon oxide SiO, wherein the carbon coating layer is doped with nitrogen and fluorine. The total mass of the silicon oxide composite material is 100.0wt%, and the mass fraction of the carbon coating layer (including N and F) is 10.0wt%. The total atomic percentage content of nitrogen and fluorine is 10.0% based on the total number of atoms of the silicon oxide composite material as 100.0%, the atomic percentage content of nitrogen is 4.0%, and the atomic percentage content of fluorine is 6.0%. The particle size of the silicon oxide composite material is 5μm; the particle size of silicon oxide SiO is 4μm.
[0083] The preparation method of the above silicon dioxide composite material is as follows:
[0084] Step 1. Prepare nitrogen-fluorine dual-doped carbon precursor solution (N, FC precursor solution).
[0085] Add 0.2 mol of p-fluoroaniline, 0.4 mol of formaldehyde solution (mass fraction of 37%) and 0.2 mol of phenol to three portions of dioxane solvent respectively, mix well, and obtain p-fluoroaniline-dioxane solution, formaldehyde-dioxane solution and phenol-dioxane solution respectively. First, add p-fluoroaniline-dioxane solution and formaldehyde-dioxane solution to a three-necked flask with a reflux device, stir at room temperature for 1 hour, slowly add phenol-dioxane solution to the three-necked flask with a constant pressure dropping funnel, stir rapidly, reflux at 95°C for 6 hours, cool naturally after the reaction is completed, remove the solvent, and use 1.0 mol·L -1 The impurities are removed by using NaOH solution and deionized water and washed to neutrality, and then placed in dioxane to form a uniform and stable clear solution, thereby synthesizing the N,FC precursor solution.
[0086] Step 2. Prepare nitrogen-fluorine dual-doped carbon-coated silicon dioxide precursor powder (N, FC@SiO precursor powder).
[0087] 0.2 mol of SiO2 was weighed and added to the N,FC precursor solution, which was sealed and ultrasonically treated for 6 h to disperse evenly, and then placed in a vacuum drying oven at 60 °C for 24 h to obtain N,FC@SiO2 precursor powder.
[0088] Step 3. Prepare nitrogen-fluorine dual-doped carbon-coated silicon oxide composite material (N, FC@SiO composite material).
[0089] The N, FC@SiO precursor powder was heated in an argon atmosphere at 4 °C min -1 The heating rate was increased from room temperature to 400 °C and maintained for 2 h, and then continued at 4 °C min -1The temperature was raised to 800 °C and maintained for 2 h, and then cooled to room temperature to obtain N, FC@SiO composite materials.
[0090] Application Example 3
[0091] A negative electrode was prepared using the N,FC@SiO composite material of Example 3 as the negative electrode active material, and then assembled into a CR 2025 button half-cell in the same manner as in Application Example 1.
[0092] Comparative Example 1
[0093] A silicon oxide composite material comprises silicon oxide SiO and a carbon coating layer coated on the surface of silicon oxide SiO. The mass fraction of the carbon coating layer is 10.0wt% based on the total mass of the silicon oxide composite material being 100.0wt%. The particle size of the silicon oxide composite material is 5μm; the particle size of the silicon oxide SiO is 4μm.
[0094] The preparation method of the above silicon dioxide composite material is as follows:
[0095] Step 1. Prepare carbon-coated silicon dioxide precursor powder (C@SiO composite precursor powder).
[0096] 0.2 mol SiO was added to the toluene solution, sealed and ultrasonically treated for 6 h to disperse evenly, and then placed in a vacuum drying oven at 60 °C for 24 h to obtain C@SiO precursor powder.
[0097] Step 2. Prepare carbon-coated silicon dioxide composite material (C@SiO composite material) by high temperature calcination.
[0098] The C@SiO precursor powder was heated in an argon atmosphere at 4 °C min -1 The heating rate was increased from room temperature to 400 °C and maintained for 2 h, and then continued at 4 °C min -1 The temperature was raised to 800 °C and maintained for 2 h, and then cooled to room temperature to obtain a C@SiO composite material.
[0099] Application Comparative Example 1
[0100] A negative electrode was prepared using the C@SiO composite material of Comparative Example 1 as a negative electrode active material, and then assembled into a CR 2025 button-type half-cell in the same manner as in Application Example 1.
[0101] Comparative Example 2
[0102] A silicon oxide composite material comprises silicon oxide SiO and a carbon coating layer coated on the surface of silicon oxide SiO, wherein the carbon coating layer is doped with nitrogen. The total mass of the silicon oxide composite material is 100.0wt%, and the content of the carbon coating layer (including N) is 10.0wt%. The atomic percentage content of the nitrogen element is 4.0% based on the total number of atoms of the silicon oxide composite material as 100.0%. The particle size of the silicon oxide composite material is 5μm; the particle size of the silicon oxide SiO is 4μm.
[0103] The preparation method of the above silicon dioxide composite material is as follows:
[0104] Step 1. Prepare N-doped carbon precursor solution (NC precursor solution).
[0105] Add 0.2 mol aniline, 0.4 mol formaldehyde solution (mass fraction 37%), and 0.2 mol phenol to three portions of toluene solvent, respectively, and mix well to obtain aniline-toluene solution, formaldehyde-toluene solution, and 2-fluorophenol-toluene solution, respectively. First, add the aniline-toluene solution and formaldehyde-toluene solution to a three-necked flask with a reflux device, stir at room temperature for 1 hour, slowly add the phenol-toluene solution to the three-necked flask with a constant pressure dropping funnel, stir rapidly, and reflux at 100°C for 6 hours. After the reaction is completed, cool naturally, remove the solvent, and use 1.0 mol·L -1 The NC precursor solution is synthesized by adding NaOH solution and deionized water to remove impurities and washing to neutrality, and then placing it in toluene to form a uniform and stable clear solution.
[0106] Step 2. Prepare nitrogen-doped carbon-coated silicon dioxide precursor powder (NC@SiO precursor powder).
[0107] 0.2 mol of SiO2 was weighed and added to the NC precursor solution, which was sealed and ultrasonically treated for 6 h to be evenly dispersed, and then placed in a vacuum drying oven at 60 °C for 24 h to obtain NC@SiO2 precursor powder.
[0108] Step 3. Prepare nitrogen-doped carbon-coated silicon dioxide composite material (NC@SiO composite material) by high temperature calcination.
[0109] NC@SiO precursor powder was heated in an argon atmosphere at 4 °C min -1 The heating rate was increased from room temperature to 400 °C and maintained for 2 h, and then continued at 4 °C min -1 The temperature was raised to 800 °C and maintained for 2 h, and then cooled to room temperature to obtain the NC@SiO composite material.
[0110] Application Comparative Example 2
[0111] A negative electrode was prepared by using the NC@SiO composite material of Comparative Example 2 as the negative electrode active material, and then assembled into a CR 2025 button-type half-cell in the same manner as in Example 1.
[0112] Performance Testing
[0113] The composite materials of Examples 1-3 and Comparative Examples 1-2 were physically characterized by SEM and EDS.
[0114] The electrochemical performance test of the batteries of application examples 1-3 and application comparative examples 1-2 was carried out: a constant current charge and discharge experiment was carried out on the batteries using a charge and discharge instrument produced by Shenzhen Xinwell, with a current density of 1000 mA g -1 (The current density of the first three cycles is 100 mAh g -1 ), the charge and discharge voltage range is 0.01-2V.
[0115] Figure 1 The scanning electron microscope (SEM) and energy spectrum (EDS) images of the N, F dual-doped carbon-coated silicon oxide composite material of Example 1 show that the N, F dual-doped carbon-coated silicon oxide composite material of Example 1 is irregular block-shaped, uniformly distributed, and has an average diameter of 5-6 μm; from the Mapping image of the EDS test, it can be seen that the N and F elements are uniformly distributed in the carbon coating layer, and the carbon coating layer acts as a shell coated on the outside of the SiO core.
[0116] Figure 2 The half-cells of Example 1 and Comparative Examples 1-2 were subjected to a current density of 1000 mAg -1 The first cycle discharge capacity of the half-cell of Example 1 is 1780 mAh g -1 , the capacity retention rate after 200 cycles is 51.76%, and the Coulomb efficiency is 99.06%.
[0117] Figure 3 The first cycle charge and discharge performance diagrams of the half-cells of Example 1 and Comparative Example 1 are shown. The reversible capacity and the first coulombic efficiency of the half-cell of Example 1 are significantly higher than those of the half-cell of Comparative Example 1.
[0118] Table 1 Electrical performance test results of half-cells of application examples 1-3 and application comparative examples 1-2
[0119] project Capacity retention rate after 200 cycles (%) Coulomb efficiency after 200 cycles (%) Example 1 51.76% 99.06% Example 2 55.28% 99.15% Example 3 51.15% 99.23% Comparative Example 1 14.39% 98.98% Comparative Example 2 45.81% 99.03%
[0120] As can be seen from Table 1, the capacity retention rate and coulombic efficiency of the half-battery of Example 1-3 after 200 cycles are higher than those of Comparative Example 1-2, indicating that the N,FC@SiO negative electrode prepared by the present invention can improve the stability of the battery, effectively inhibit the volume expansion of silicon dioxide particles during charging and discharging, and reduce the capacity loss of the battery during the cycle process, laying a foundation for the industrial production of silicon-carbon batteries.
[0121] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0122] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A silicon oxide composite material, characterized in that: It comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, wherein the carbon coating layer is doped with nitrogen and fluorine.
2. The silicon dioxide composite material according to claim 1, characterized in that: Based on the total mass of the silicon oxide composite material being 100.0 wt %, the mass fraction of the carbon coating layer is 5-14.0 wt %.
3. The silicon dioxide composite material according to claim 1 or 2, characterized in that: Taking the total atomic number of the silicon oxide composite material as 100.0%, the atomic percentage content of the nitrogen element is 0.1-5.0%, and the atomic percentage content of the fluorine element is 0.1-5.0%.
4. The silicon dioxide composite material according to claim 1 or 2, characterized in that: The particle size of the silicon monoxide composite material is 4.5-20 μm; the particle size of the silicon monoxide is 4-10 μm.
5. The method for preparing the silicon dioxide composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1. Mix a carbon source, a nitrogen source and a fluorine source, react under heating conditions, and then cool and wash the reaction product and mix it with a solvent to obtain a nitrogen-fluorine doped carbon precursor solution; Step 2. mixing silicon dioxide with the nitrogen-fluorine-doped carbon precursor solution, and drying to obtain nitrogen-fluorine-doped carbon-coated silicon dioxide precursor powder; Step 3: calcining the nitrogen-fluorine-doped carbon-coated silicon oxide precursor powder in an inert gas atmosphere to obtain a nitrogen-fluorine-doped carbon-coated silicon oxide composite material.
6. The method for preparing the silicon dioxide composite material according to claim 5, characterized in that: In step 1, primary amine compounds, formaldehyde and phenol compounds are mixed with the solvent respectively to obtain primary amine compound solution, formaldehyde solution and phenol compound solution, wherein the primary amine compound and / or the phenol compound contain fluorine; the primary amine compound solution, formaldehyde solution and phenol compound solution are mixed and reacted under heating conditions, and then the reaction product is cooled, washed and mixed with the solvent to obtain the nitrogen-fluorine-doped carbon precursor solution.
7. The method for preparing the silicon dioxide composite material according to claim 6, characterized in that: In step 1, the primary amine compound is aniline and / or p-fluoroaniline; and / or the phenol compound includes at least one of phenol, 2-fluorophenol and p-trifluoromethylphenol; and / or the solvent includes at least one of toluene, dioxane, chloroform and DMF.
8. The method for preparing the silicon dioxide composite material according to claim 6, characterized in that: In step 1, the molar ratio of the primary amine compound, the formaldehyde and the phenol compound is (0.8-1.2):(1.8-2.2):(0.8-1.2); and / or, the reaction is carried out at 90-100° C. for 5-6 hours.
9. The method for preparing the silicon dioxide composite material according to claim 6, characterized in that: In step 2, the molar ratio of silicon dioxide to the primary amine compound is 1:1-1:
3.
10. The method for preparing the silicon dioxide composite material according to claim 5 or 6, characterized in that: In step 3, a pre-sintering treatment is first performed at 380-420° C. for 1.5-2.5 h, and then a calcining treatment is performed at 400-900° C. for 1.5-2.5 h.
Citation Information
Patent Citations
Preparation method and application of carbon-coated silicon monoxide material
CN110148729A
Carbon-coated silicon oxide negative electrode material as well as preparation method and application thereof
CN110176601A
A carbon-coated core-shell structured silicon suboxide / silicon composite material and its preparation method
CN112289993B
Silica material as well as preparation method and application thereof
CN113471440A
Preparation method of phosphorus-doped porous carbon coated silicon monoxide material, and product thereof
CN113816384A